Physician Executive Leadership Plus: An Approach to Business and Management Education for Medical Students - Stephanie R. Beldick (SAGE Publishing, 2021)
INTRODUCTION Physicians are looked upon to lead the healthcare team, a task that has grown increasingly complex and interdisciplinary, requiring a diverse extra-clinical skillset. Physician Executive Leadership (PEL) Plus is a student-run program that uniquely utilizes both didactic and real-world project-based approaches to deliver a business and management curriculum to medical students. METHODS We developed and implemented PEL Plus during the 2018-19 and 2019-20 academic years, geared at first- and second-year medical students. We provide an overview of this combined didactic and project-based curriculum, in addition to evaluating if the program was efficacious in teaching the desired skillset. We assessed short-term knowledge acquisition using multiple-choice questions, and investigated student perceptions of their learning and the program using Likert scales and narrative feedback. We also investigated the influence of student demographics on performance, in order to assess the appropriateness of our target audience. RESULTS 28 students completed PEL Plus over the two years (14 students/year). Average performance on multiple-choice questions showed statistically significant improvement after the majority of sessions. There were no statistically significant effects of demographics on performance in the majority of sessions. Students self-rated stronger understandings of lecture topics after each session, and analysis of narrative feedback demonstrated thematic categories centred on teaching style, new knowledge, lecture content/material, projects, networking, program structure, and generic statements. DISCUSSION PEL Plus is an innovative and effective approach to teaching business, leadership, and management skills in undergraduate medical education. Development of similar programs at other institutions will positively impact the broader medical student community.